Eco-friendly approach to corrosion inhibition of aluminum by Congo red dye in alkaline media: Experimental assessment, QSAR modeling, diffusion studies, and DFT/MC/MD simulations - Ayoub Chahid; Said Meftah; Mohamed Essahli; Mohammed Chafi; Rachid Kellal; Driss Benmessaoud Left; Mustapha Zertoubi (Hybrid Advances)
Aluminum corrosion in alkaline media poses a significant limitation for its industrial use. This study proposes a comprehensive multi-scale approach to evaluate Congo Red dye (DRC) as an eco-friendly and efficient corrosion inhibitor for aluminum in 1.0 M NaOH. The work combines experimental techniques, quantum chemical calculations, and advanced modeling tools to provide detailed mechanistic insights. Weight loss measurements showed a maximum inhibition efficiency of 87.5 % at 1200 ppm, with decreased efficiency at higher temperatures, indicating a physical adsorption mechanism. The thermodynamic analysis confirmed the spontaneous and endothermic nature of the process. SEM analysis revealed the formation of a dense protective film on the aluminum surface. DFT and DFTB+ calculations identified key adsorption centers through Mulliken charges, MEP maps, and Fukui functions. COSMO-RS and sigma profile analysis revealed favorable solvation and hydrogen-bonding behavior. A QSAR model, built using the Genetic Function Approximation (GFA) method and descriptors from eight azo dyes, achieved a strong predictive correlation (R2 = 0.95). Monte Carlo and Molecular Dynamics simulations confirmed stable adsorption of DRC on Al(111) and Al2O3(111), with adsorption energies around −130 kcal/mol. Diffusion studies using Mean Square Displacement (MSD) and Fractional Free Volume (FFV) demonstrated the inhibitor film's ability to restrict the mobility of aggressive species (H2O, OH−, Na+, O2), highlighting its effectiveness in blocking ion transport and limiting corrosion. This study emphasizes the value of combining theoretical modeling with experimental validation and presents Congo Red dye as a sustainable and high-performance corrosion inhibitor for aluminum in alkaline environments.